(untitled) (American International Journal of Supply Chain Management, 2020)
The tremendous delayed in the payment of salaries and wages to civil servants in Cross River State is an imperative challenge crushing and knocking down the corporate as well as workers’ performance of ministries, institutions and agencies in the system. Salaries and wages structure are always established haphazardly and arbitrarily. This results in salaries and wages inequities, which are the most dangerous sources of friction, conflict and low morale in organizations. It has also created negative attitudes of workers towards their jobs and responsibilities in organizations. This study adopted survey research design. The population 1206 which consist of the various workers of the Cross River State Civil Service Commission that cut across ministries, agencies, institutions and other parastatals. Simple random sampling technique was applied through the use of Taro Yamane formula in determining the sample size of 234 respondents. Primary data was collected through the use of a structured questionnaire using 4 points Likert scale of strongly agreed (4), agreed (3), and disagreed (2), strongly disagreed (1). The data analysis technique used for the study was linear regression model, including ordinary least square and analysis of variance (ANOVA) through SPSS version 20, to test the hypotheses. The study revealed that salaries and wages management significantly influence the development of organizational performance of the Cross River State ministries, agencies and institutions. Early payments of salaries and wages have a significant influence on organizational performance in the state. The amount of salaries and wages paid also has a significant effect on workers’ involvement, loyalty and commitment of the state. Salaries and wages structure also have a significant influence on organizational job satisfaction of the state. Salaries and wages management also contributes to workers’ motivation and morale in the state. The study recommended that management as well as administrators of the various ministries and institutions should ensure that their workers are financially satisfied at when due in their payment of wages and salaries, if they are to be motivated, committed and loyal, satisfied on the job performance and productivity. This is because financially satisfied workers will be more motivated, productive, engaged and emotionally attached to the organizational jobs.